Increasing the Capacity and Quality of Cheisya Kitchen’s Milkfish Processing with Technology and Innovation - Ikmal, Novita Maulida; Hardaningtyas, Dwi; Subaderi, Subaderi (Jurnal Pengabdian UNDIKMA, 2025)
This community service program aimed to enhance the capacity and quality of processed milkfish products through technology utilization and product diversification innovation. The implementation methods were oriented toward solving priority problems through ergonomics training, social media marketing training, assistance in obtaining halal certification, and technology transfer in the form of a pressure cooker and charcoal grill. The intervention focused on three main problem areas: production, marketing, and management. The results of the program showed a significant improvement in the production capacity of the Cheisya Kitchen business with the provision of Appropriate Technology (AT) equipment, namely a 20-kg capacity pressure cooker and a 60×40×85 cm charcoal grill machine. Production capacity increased by approximately 50% among three assisted partners. In terms of efficiency, the use of these machines enabled larger-scale production within shorter processing times. Partners also received training on operating the AT machines to ensure sustainable use. From a quality perspective, ergonomics training helped partners organize the production process more effectively. Furthermore, the processed milkfish products successfully obtained halal certification, enabling their distribution through online sales platforms. Partners were also trained and mentored in packaging using a vacuum sealer and in digital marketing through TikTok and Shopee, contributing to increased market reach and business competitiveness.